Determinants of Iron Supplementation Compliance Among Adolescent Girls in Kuningan Regency, Indonesia - Ramdhani, Nur Laily; Dwiriani, Cesilia Meti; Khomsan , Ali (Journal of Health and Nutrition Research, 2025)
The iron supplementation program is one of the efforts to overcome anemia based on WHO recommendations. The compliance of iron supplement consumption is an indicator of the success of anemia prevention programs. This cross-sectional study aims to analyze factors related to compliance with iron supplement consumption among adolescent girls in health center areas in Kuningan Regency. The study involved 105 respondents selected using a proportional random sampling technique. Data were collected using a questionnaire for each variable. The data were analyzed using Chi-Square statistical test. The results showed that only 21% of adolescent girls were found to be compliant in taking iron supplements. Approximately 62.9% of adolescent girls with good knowledge were compliant in taking iron supplements (p=0.041). 70.4% of adolescent girls with positive attitudes were compliant in taking iron supplements (p=0.018). Approximately 50.6% of adolescent girls lacked support from teachers (p=0.019), 71.1% lacked support from peers (p=0.010), and 62.7% lacked access to nutrition education or counseling at school (p=0.010). This study suggests the need of cross-sectoral support from both the health and education sectors to strengthen the implementation of the routine iron tablet consumption program as recommended.